Sistem Monitoring Kwh Meter Analog Berbasis SMS Gateway - Pratama, Rian; Tifani, Vanessa Chita; Djatmiko, Wisnu (LPPM Universitas Negeri Jakarta, 2015)
In the daily life of society we must recognize a device called KWH analog meter, which is a tool used by PT. PLN (Persero) to calculate the power consumption of consumers. But this time KWH existing analog meter does not notify large electric power and the cost we have to pay clearly. So we made